2021
DOI: 10.1136/bmjopen-2020-039670
|View full text |Cite
|
Sign up to set email alerts
|

Patient and parent perspectives on transition from paediatric to adult healthcare in rheumatic diseases: an interview study

Abstract: ObjectivesTo describe the experiences, priorities, and needs of patients with rheumatic disease and their parents during transition from paediatric to adult healthcare.SettingFace-to-face and telephone semistructured interviews were conducted from December 2018 to September 2019 recruited from five hospital centres in Australia.ParticipantsFourteen young people and 16 parents were interviewed. Young people were included if they were English speaking, aged 14–25 years, diagnosed with an inflammatory rheumatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Almost all studies used a semi-structured interview [ 38 40 ], but a few studies conducted an unstructured interview [ 41 ]. Furthermore, the majority of interviews were held face-to-face in the clinical setting [ 37 39 ] or at the patients’ home [ 40 ], and a few interviews were conducted by telephone [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies used a semi-structured interview [ 38 40 ], but a few studies conducted an unstructured interview [ 41 ]. Furthermore, the majority of interviews were held face-to-face in the clinical setting [ 37 39 ] or at the patients’ home [ 40 ], and a few interviews were conducted by telephone [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tele-rheumatology is a resource that can be valuable for this population as it can be used when patients are away for university/college for follow-up appointments and make it easier to have joint appointments with health care providers. A transition navigator or coach may be a valuable resource to bridge the divide between pediatric and adult care, provide psychosocial support to young adult patients, and provide continuity to patients during this challenging time [ 20 , 21 ]. Transition navigators have been found to improve adherence to medication, attendance at clinic, and reduce acute complications of disease in other chronic disease populations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Themes and sub-themes identified had support as well in previous qualitative studies as synthesized in a 2020 systematic review which included 16 studies. Preparedness for transition [ 17 , 33 ], readiness for transfer of care [ 17 ], developing self-advocacy skills [ 17 ], continuity and breadth of care [ 17 , 33 ], changing relationships [ 17 ], culture shock [ 17 ], new responsibilities [ 17 ], need for support [ 17 ], social support [ 17 , 34 ], while additional emphases were identified by this study on mental health support and ongoing support needs – beyond the transfer of care. The Kelly et al systematic review [ 17 ] identified support for the whole person (theme of deprived of human focus) which encompasses psychological support, but did not explicitly identify mental health support [ 17 ].…”
Section: Discussionmentioning
confidence: 99%